Performance Review of Multiple Reference Versus Time Domain Optical Coherence Tomography - Kai Neuhaus; Paul M. McNamara; Sergey Alexandrov; Sean O'Gorman; Josh Hogan; Carol Wilson; Martin J. Leahy (IEEE Photonics Journal, 2018)
We present a detailed characterization of noise sources in multiple reference optical coherence tomography (MR-OCT) compared to time-domain OCT (TD-OCT). The noise characteristics were modeled based on the TD-OCT noise model and modified for MR-OCT and confirmed with measurements. The MR-OCT sensitivity characteristics are significantly affected by the reflection from the partial mirror, which also introduces a natural attenuation in the reference arm, partially matching the reflectivity intensity profile of human tissue. At optimal balance between sample and reference arm and using balanced detection, the peak sensitivity was measured to be 95 dB, which is close to simple Fourier-domain systems. The results provide a better understanding of the application range for MR-OCT and higher order effects observed, suggesting a nontrivial noise model for MR-OCT.